Legal Analysis of the Freedom of Contract Principle in Lease Contracts between the Director General of Civil Aviation and Private Flight Schools - Pandini Febrianti Islami Putri, Intan; Sutrisno, Endang; Sutarih, Ayih (Ann Publisher, 2023)
In accordance with an open system, everyone is permitted to enter into an agreement so long as it is founded on good faith, according to Indonesian treaty law. This approach is not entirely relevant in the practice of lease agreements held by the government (Director General of Civil Aviation) with private parties (Private Flight Schools), as the lease agreement was made in a way that the terms were made by default. In order to collect secondary data in the form of primary and secondary legal materials, this research employs a normative juridical approach, law-based research as norms and rules that are both written and unwritten through literary studies, and document studies. The findings revealed that the format of common lease agreements negotiated between the government (Director General of Civil Aviation) and private parties (Private Flight Schools) was subject to constraints. This demonstrates how the idea of complete contract freedom is not being applied. The posture or bargaining position between the parties to the agreement is not balanced, which gives the airport with a stronger position options. As a result, the airport's rules and regulations have an impact on the tenant's rights.